Scientific expeditions in XIXth century: the universe of science and the cultural diversity - Fetz, Marcelo (Faculdade de Ciências e Letras - Unesp - Araraquara., 2012)
The present paper develops to realize a sociological analysis of the scientific context of the beginning of nineteenth century in Brazil. As a hegemonic discourse, the scientific narrative of the expeditions appears connected with the pictorial art in a literature structure. Science, art and literature, thus, were utilized as a methodological way to justify and to legitimize the scientific discourse. Therefore, our objective in this paper is to realize a brief study of the travel narratives, as well the connection of the science with art and literature in a social context that promoted a naturalized representation of the cultural diversity. Through a historical sociology of science and a historical cultural study we aim to contribute to the elucidation of “a vision of the world” that intermediate the scientific representation of the social differences in nineteenth century.